The "powtoon" technique in the skill of speaking speech - Patiño-Ramírez, Cecilia (2020)
The research aimed to demonstrate how the use of the Powtoon technique improves the speaking ability of "speaking" in Foreign Language Students IV - Implemented. The specific method of the investigation was the experimental one, using a quasi-experimental design with a control group and an experimental group, with pre and post test. The sample consisted of 30 students, these students belonged to the Physical Education School Implemented, 15 students from the experimental group and 15 students from the control group. After applying the class sessions, it was concluded that the Powtoon technique significantly improves the speaking ability in students, as demonstrated by the inferential test "Spearman's Rho", Applied statistically and with α = 0.05.